gtrellis: an R/Bioconductor package for making genome-level Trellis graphics - Gu, Zuguang; Eils, Roland; Schlesner, Matthias (BMC bioinformatics, 2016)
Trellis graphics are a visualization method that splits data by one or more categorical variables and displays subsets of the data in a grid of panels. Trellis graphics are broadly used in genomic data analysis to compare statistics over different categories in parallel and reveal multivariate relationships. However, current software packages to produce Trellis graphics have not been designed with genomic data in mind and lack some functionality that is required for effective visualization of genomic data.